The effect of biological heterogeneity on R-CHOP treatment outcome in diffuse large B-cell lymphoma across five international regions. Issue 5 (4th May 2017) - Carr, Robert; Ozdag, Hilal; Tekin, Nilgun; Morris, Timothy; Conget, Paulette; Bruna, Flavia; Timar, Botond; Gagyi, Eva; Basak, Ranjan; Naik, Omkar; Auewarakul, Chirayu; Srithana, Narongrit; et al.
Abstract: Addressing the global burden of cancer, understanding its diverse biology, and promoting appropriate prevention and treatment strategies around the world has become a priority for the United Nations and International Atomic Energy Agency (IAEA), the WHO, and International Agency for Research on Cancer (IARC). The IAEA sponsored an international prospective cohort study to better understand biology, treatment response, and outcomes of diffuse large B-cell lymphoma (DLBCL) in low and middle-income countries across five UN-defined geographical regions. We report an analysis of biological variation in DLBCL across seven ethnic and environmentally diverse populations. In this cohort of 136 patients treated to a common protocol, we demonstrate significant biological differences between countries, characterized by a validated prognostic gene expression score ( p < .0001), but International Prognostic Index (IPI)-adjusted survivals in all participating countries were similar. We conclude that DLBCL treatment outcomes in these populations can be benchmarked to international standards, despite biological heterogeneity.